The Role of Productive Waqf for Public Welfare (Study Case of Nadzir Foundation In University of Islam Malang) - Rofai, Yuli; Burhan, Umar; Multifiah, Multifiah (International Journal of Social and Local Economic Governance, 2016)
Productive Waqf for VIP room (Very Important Person) in RSI Malang (Islamic Hospital of Malang) which is managed by the foundation of Nadzir in Universiy of Islam Malang is a pilot project of productive waqfÂ  that comes from the grants provided by the Ministry of Religious Affairs. The public strongly supports Productive Waqf for VIP room in RSI Malang and make the VIP room is never empty. So that in less than 7 (seven) years the VIP building have reached BEP (Break Event Point). Nadzir foundation of Universiy of Islam Malang is also developing productive waqf by adding a VIP room and build a minimarket Al Khaibar. The existence of a pilot project of productive waqf VIP room and minimarket is perceived by the public. The construction of the VIP room in RSI Malang and minimarket create new jobs for the people. Productive waqf which is managed Nadzir foundation in University of Islam Malang is expected to be ableÂ  to continue the developing and give more benefit to society.Keywords: Productive waqf, Welfare, Nadzir